Offshore Technology Conference 2006
DOI: 10.4043/17986-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predicting, Measuring and Implementing Friction and Bending Stresses in Dynamic Umbilical Design

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA model for predicting dynamic umbilical stresses due to friction, elastic bending and tension has been developed and compared with strain gauge data from full scale dynamic testing. The results have been used to develop effective stress and fatigue analysis procedures that can be applied for both extreme and fatigue design. These procedures have been applied for both extreme and fatigue design cases to demonstrate the importance of different physical effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The differences between the two results are attributed to the fact that the radius reduction of helical tendon is neglected in the analytical model, which is induced by the contractions of central assembly and insertions of the helical tendon with the sheaths. The similar trends and differences have also been reported by reference (Ekeberg et al (2006)). To consider the effect of the radius reduction of helical tendon, a modify axial stiffness formula has been introduced as…”
Section: Stepsupporting
confidence: 90%
See 1 more Smart Citation
“…The differences between the two results are attributed to the fact that the radius reduction of helical tendon is neglected in the analytical model, which is induced by the contractions of central assembly and insertions of the helical tendon with the sheaths. The similar trends and differences have also been reported by reference (Ekeberg et al (2006)). To consider the effect of the radius reduction of helical tendon, a modify axial stiffness formula has been introduced as…”
Section: Stepsupporting
confidence: 90%
“…From their results, axially symmetric relationships between the axial loads and the strains have been found; and the prediction achieved good agreements with experimental results. However, when it comes to the Corresponding author, Professor, E-mail: shixiao.fu@sjtu.edu.cn tensional stiffness of the un-bonded umbilical, the effects of the radius reduction caused the predicted result 2-4 times larger than the experimental result (Ekeberg et al 2006). As for the bending properties of the multi layer structures, more difficulties is confronted with due to the large nonlinearity behaviors caused by the sliding of the helical components.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, static and dynamic friction coefficients and the corresponding smooth transition between these two friction coefficients were observed by Rabinowicz [8] in some tests. Several works have been reported in the literature, see [3,9,10,11,12,13], concerning the hysteric bending behavior of helix elements versus full scale tests. Most of the work demonstrated that good correlation in terms of axial stress of helix elements and hysteresis bending moment-curvature relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting, Measuring and Implementing Friction Stresses in dynmaic analysis is performed in this study bu Abaqus's sub-modelng and conact definition. However, this issue was dealt using a different approach in [6].…”
Section: Remarksmentioning
confidence: 99%